Georg Venzkys geschickter Übersetzer. Vom Nutzen und Nachteil der Historie für die Translationswissenschaft - Boguna, Julija (chronotopos – A Journal of Translation History, 2019)
In 1734, the first seperate treatise on translation theory written in German was published in Gottscheds „Beyträge zur critischen Historie der deutschen Sprache, Poesie und Beredsamkeit“ – Georg Venzky’s „Das Bild eines geschickten Übersetzers“. This paper presents the main features of this treatise. It focuses on the location of this treatise in historical representations of translation (usually literary history). The main emphasis will be on translation-historiographical considerations using the example of Venzky and his “image”, and the usefulness of a meta-historiographical perspective for translation studies. Furthermore, but to a lesser extent, the benefit of a metahistoriographical perspective for translation didactics will be discussed. This will be done in the context of the demand for the “humanization” of the history of translation (Pym) and the implementation of this demand in the translation-historical research currently establishing itself – also by using the example of the Germersheim Translator's Dictionary.